Kirjanpitotilojen tuloksia: tilivuodet 1996 ja 1997 - Tauriainen, Jukka; Mäkelä, Terhi; Eskola, Katri; Knaapinen, Petri (Maatalouden taloudellinen tutkimuslaitos, 2000)
The results of agricultural profitability research in Finland in 1996 and 1997 are presented in this report. The number of farms entering the research was 983 in 1996 and 1082 (including 113 horticulture enter-prises) in 1997. The bookkeeping information about horticulture enter-prises has been gathered since the year 1996. The economic results of these enterprises from the year 1996 has been published in Institutes Working papers 7/98. The profitability research is organized on voluntary basis. The results are considered to represent effective and full-time family farming in Finland. The results are presented for all farms in average and grouped according to size and type of the farm. Results for primary production types are also presented according to the subsidy areas. In the result calculation the data on greenhouse and outdoor vegetable production was weighted according to production lines and size classes in the FADN system.
Maatalousosion on laatinut Jukka Tauriainen, taulukot ovat koonneet Terhi Mäkelä ja Katri Eskola, joka on myös taittanut julkaisun. Puutarha-aineiston on koonnut Petri Knaapinen.
Keywords: Ma; kirjanpito; puutarhanhoito; tulot; kannattavuus; kustannukset; laskentatoimi; kannattavuustutkimus; accounting; bookkeeping; farm results; horticulture; income; profitability; costs